Formation process and controlling factors of tight buried-basement hill reservoirs:a case study of Weixinan Depression, Northern Beibu Gulf Basin, South China - Li, Anran; Xu, Fanghao; Fan, Caiwei; Li, Ming; Jiang, Fan; Xu, Guosheng; Xiong, Xiaojun; Zhang, Xichun; Xie, Bing (Frontiers in Earth Science, 2025)
In relatively stable sedimentary basins, the formation of buried-basement hill reservoirs mainly occurs after the basin basement forms and before the overlying sedimentary cover layer is filled. Represented by the Beibu Gulf Basin in the South China Sea, buried-basement hill reservoirs are key targets for hydrocarbon exploration in deep sedimentary basins. Limited exploration and research in buried-basement hills hinder the understanding of hydrocarbon accumulation conditions, thereby restricting large-scale hydrocarbon exploration. Geophysical methods, including the balanced section method and stress field analysis, were used to restore the formation and burial processes of buried-hills in the Weixinan Depression of Beibu Gulf Basin. The formation process of these buried-basement hills consists of five stages including diapiric uplift (Caledonian period), thrust (Indosinian-Yanshanian period), multiple exposure (Late Caledonian, and Indosinian-Yanshanian period), multiple burials (Hercynian period and Early Himalayan Period), and finalization (Late Himalayan Period). Three controlling factors of these buried-basement hills are determined: ①differences in the degree of granite intrusion lead to differences in karst paleogeomorphology; ②thrust movement of NE-SW direction during the Hercynian period; ③ thrust movement of NW-SE direction during the Indosinian-Yanshanian. The main controlling factors for the development of buried-carbonate basement hill reservoirs are multi-stage tectonic stress, karstification, and lithology. The tight buried-carbonate hill reservoir mainly composed of dissolved pore and fracture is concentrated in horizontal underflow zone. The main controlling factors for the development of buried-granite (or metamorphic rock) hill reservoirs are tectonic stress, and karstification. The reservoir mainly composed of dissolved pore and fracture is concentrated in leaching zone located at the top of each buried-granite and metamorphic rocks hill.